Normal Tension Glaucoma - Mir Zaman, Mohammad Daud Khan, Tariq Farooq Babar, Muhammad Tariq Khan (Pakistan Journal of Ophthalmology, 2006)
Normal tension glaucoma (NTG), also called as low-tension glaucoma, continues to be a diagnostic and therapeutic challenge even in the new millennium. NTG can be differentiated from primary open angle glaucoma by having an infero-temporally displaced large cup, notching of the neuro-retinal rim in the infero-temporal quadrant, decreased nerve fiber layer (NFL) thickness, flameshaped disc hemorrhage on temporal side and visual field defects steeper sided & deeper and within five degrees of fixation. Risk factors for normal tension glaucoma include, females aged 60 years or above, history of peripheral vascular spasm in cold, migrainous headaches and nocturnal systemic hypotension. Ocular examination includes measuring intraocular pressure environment central corneal thickness and paying attention to the optic disc, neuro-retinal rim, NFL thickness & visual fields. Neuro-imaging is required only in specific cases. Polymorphisms in the OPA1 gene is considered to be a marker for this disease. Careful screening in positive families may detect disease at an earlier stage. Treatment modalities include differentiating non-progressive from progressive form of normal tension glaucoma. Progressive form requires intra-ocular pressure reduction by 30% by medical or surgical treatment. Betaxolol, latanoprost and dorzolamide are effective as they can increase optic nerve blood flow. Trabeculectomy can be offered when there is progressive visual field loss in spite of intra-ocular pressure being in the lower teens.